Novel insights into the ontogeny of basophils - Miyake, Kensuke; Ito, Junya; Karasuyama, Hajime (Frontiers in Allergy, 2024)
Basophils are the least common granulocytes, accounting for <1% of peripheral blood leukocytes. In the last 20 years, analytical tools for mouse basophils have been developed, and we now recognize that basophils play critical roles in various immune reactions, including the development of allergic inflammation and protective immunity against parasites. Moreover, the combined use of flow cytometric analyses and knockout mice has uncovered several progenitor cells committed to basophils in mice. Recently, advancements in single-cell RNA sequencing (scRNAseq) technologies have challenged the classical view of the differentiation of various hematopoietic cell lineages. This is also true for basophil differentiation, and studies using scRNA-seq analysis have provided novel insights into basophil differentiation, including the association of basophil differentiation with that of erythrocyte/megakaryocyte and the discovery of novel basophil progenitor cells in the mouse bone marrow. In this review, we summarize the recent findings of basophil ontogeny in both mice and humans, mainly focusing on studies using scRNA-seq analyses.